Sosialisasi Edukasi Varian Baru Covid-19 dan Pentingnya Vaksinasi Guna Mencegah Penyebaran Virus Covid-19 di Desa Songbledeg, Wonogiri - Ketrin Agnia Rahmani Putri; Yudi Rinanto; Isna Nurmilatul Azizah; Isnanda Nur Ramdani; Cahya Sukma Baiti Arniwa; Afifah Wahyuning Ramadhany (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
This community service activity aims to increase knowledge and understanding of the community in Songbledeg Village about the new variant of covid-19 and the importance of vaccination. This socialization activity is carried out offline by applying health protocols, so that the people present are only representatives of each hamlet only. The people who attended were very participating in a series of socialization events and actively asked questions to the speaker. This socialization activity is useful for the community so that it is more understanding about the prevention of transmission and handling new variants of covid-19. In addition, the public becomes more aware of the importance of Covid-19 vaccination to increase immunity to the Covid-19 virus. Socialization activities that have been carried out by the KKN team have increased the knowledge of the people of Songbledeg Village about the new variant of Covid-19 and how to prevent it, and has increased public knowledge about the importance of Covid-19 vaccination.